Steps to achieve carvone-rich spearmint (Mentha spicata L.) essential oil: a case study on the use of different distillation methods - Moradi-Sadr, Jalil; Ebadi, Mohammad-Taghi; Ayyari, Mahdi (Frontiers in Plant Science, 2023)
Spearmint essential oil is a valuable medical and food product. Spearmint essential oil is effective for the treatment of flatulence, indigestion, nausea, and colic along with Alzheimer, obesity, and fungal infections. This study evaluated the quality and quantity of spearmint essential oil by examining some extraction strategies. The procedures were hydro-distillation, hydro-steam distillation, microwave-assisted hydro-distillation, and open hydro-distillation. The hydro-distillation had five pH levels (2, 4, 6, 8, and 10) and four NaCl concentrations (0.5, 1, 1.5, and 2%). microwaveassisted hydro-distillation at a power of 225 W was applied for 60, 90, and 120 minutes for process durations. The solvent extraction of herbal distillate obtained by an open hydro-distillation system was done using n-pentane and n-hexane to achieve a recovered essential oilby a rotary evaporator. The results showed that the lowest pH in the hydro-distillation process led to obtaining double yield compared to the control. Additionally, at 1 and 1.5% NaCl concentrations, the oil yield increased by 12.86 and 20.87%, respectively. Although the yield was reduced by microwave-assisted hydrodistillation, however within 120 minutes, carvone increased by 12.7% and limonene decreased by 42.3%. The best quality of spearmint oil belonged to solvent extraction followed by rotary evaporator.